Nanotechnology for treatment of stroke and spinal cord injury - Kubinová, Sárka; Syková, Eva (Nanomedicine (London, England), 2010)
The use of nanotechnology in cell therapy and tissue engineering offers promising future perspectives for brain and spinal cord injury treatment. Stem cells have been shown to selectively target injured brain and spinal cord tissue and improve functional recovery. To allow cell detection, superparamagnetic iron-oxide nanoparticles can be used to label transplanted cells. MRI is then a suitable method for the in vivo tracking of grafted cells in the host organism. CNS, and particularly spinal cord, injury is accompanied by tissue damage and the formation of physical and biochemical barriers that prevent axons from regenerating. One aspect of nanomedicine is the development of biologically compatible nanofiber scaffolds that mimic the structure of the extracellular matrix and can serve as a permissive bridge for axonal regeneration or as a drug-delivery system. The incorporation of biologically active epitopes and/or the utilization of these scaffolds as stem cell carriers may further enhance their therapeutic efficacy.
Keywords: nanotechnologie; poranění míchy; zvířata; Humans; Stroke; Nanotechnology; Spinal Cord Injuries; cévní mozková příhoda; Nanomedicine; lidé; nanomedicína; Animals